Etnografia das memórias cinematográficas no vale do Mamanguape-PB - Falcão Neto, Jose Muniz (2019)
This research seeks to ethnographically address the memories related to cinema experiences in small towns in the interior of Brazil, specifically in Mamanguape and Rio Tinto, north coast of Paraíba state. Film screenings at Cine Eldorado and Cine Orion in the second half of the twentieth century are still alive in the memories of locals, currently shared through the world wide web. Methods and concepts associated with visual anthropology (photo and video elicitation, film analysis, virtual ethnography) are articulated with reflections pertinent to the history of cinema to question the experiences of expectoriality in interior cinemas and their specificity as expressions of modernity and coloniality. The anthropology dedicated to the study of cinema, such as MasimoCanevacci and, more recently, Rose Satiko, adds to the ethnographic perspective of approaching the memories of former workers and public of the interior cinemas, with which an ethnographic film was made, designed on the basis of participatory camera (Jean Rouch) and direct cinema notions. Thus, this dissertation seeks to dialogue with authors and postcolonial critiques in the consideration of cinema and modernity, reflected in the experience of the subjects approached in relation to their previous experiences in the old (now deactivated) local cinemas. The approach of cinema as a technical image, in VilémFlusser's sense, was also relevant to think about the duration of cinema from contemporary screens of computers and smartphones. How, therefore, the cinema contributed, in the mid-twentieth century, to “modernize”, “enchant” or “catechize” a population composed largely of rural and indigenous workers, admitted to an industrialized urban work regime (marked by a factory)? To what extent, then, can thinking of film projections and receptions in small cities allow us to elaborate critical dimensions of living conditions in postcolonial societies?